The Effect of a Short Animation Movie Towards Students’ Achievement - Serlia Laeka; Vivin Krismawanti Modjanggo (Sintuwu Maroso Journal of English Teaching, 2022)
The objective of this research is to know the effect of a short animation movie in learning English to find out students’ achievement in writing at tenth TKJ grade in SMK GKST Poso. The Method of this research is a pre-experimental research, one group pretestposttest, which has done in 5 meetings. In first meeting the researcher give a pre-test to know students’ initial achievement in writing narrative text, entilted, “Malin Kundang”. In second until fourth meetings the researcher give a treatment in implementing the shortanimation movie learning media and give a post-test in the fifth meeting to find out student’ final achievement after giving a treatment. The result of this research shows that there is a significance effect towards students’ achievement in writing narrative text using a short animation movie as a learning media. It can be seen from, paired sample t-test, the sig. (2tailed)is 0,000. It means that,the sig. (2-tailed) < 0,05. The result of the research shows, a significant effect with the sig. (2-tailed) 0,000 < 0,05. The result of testing the hypothesis shows that the null hypothesis is rejected and the alternative hypothesis is accepted. It means that there is a significant effect in using a short animation movie towards students achievement in writing narrative text.